A 1, 1′-vinylene-fused indacenodithiophene-based low bandgap polymer for efficient polymer solar cells. Issue 10 (22nd February 2017) - Fan, Qunping; Su, Wenyan; Guo, Xia; Zhang, Xi; Xu, Zhuo; Guo, Bing; Jiang, Lang; Zhang, Maojie; Li, Yongfang
Abstract : A ladder-type polymerPIDTV-ffBT based on a 1, 1′-vinylene-fused indacenodithiophene donor unit and a fluorinated benzothiadiazole acceptor unit was synthesized. The PSCs based onPIDTV-ffBT :PC71 BM achieved a PCE of 7.3% with a high J sc of 17.1 mA cm −2, which is the highest J sc reported for ladder-type polymer-based PSCs. Abstract : A 1, 1′-vinylene-fused indacenodithiophene (IDTV ) donor unit with 22 π-conjugated electrons was synthesized. A ladder-type D–A copolymerPIDTV-ffBT usingIDTV as the donor unit and 5, 6-difluorobenzothiadiazole (ffBT) as the acceptor unit was developed for application as a donor material in polymer solar cells (PSCs). Compared to other analogue polymers, PIDTV-ffBT possesses a two-dimensional conjugated multi-electron fused ring, excellent planarity and close π–π stacking, leading to a higher light harvesting coefficient, an enhanced charge carrier mobility of 0.032 cm 2 V −1 s −1 and improved photovoltaic performance. The PSCs based onPIDTV-ffBT :PC71 BM achieved a promising power conversion efficiency (PCE) of 7.3% with a high short-circuit current density ( J sc ) of 17.1 mA cm −2 . These results indicate that the introduction of the 1, 1′-vinylene-fused system intoIDTV for ladder-type polymers is an effective strategy to enhance the light absorption coefficient and improve charge carrier mobility for high efficiency PSCs.